Perancangan dan Implementasi Sistem Otomatisasi Pemesanan dan Pembayaran untuk Layanan Rental Berbasis Web: Studi Kasus WIBUCOSRENT - Muhammad Syahrul Haniawan; Hardika Khusnuliawati; Astri Charolina (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The costume rental management process often faces challenges in operational inefficiency and limitations in providing an optimal user experience. This research aims to develop and evaluate a web-based costume rental information system for the Wibucosrent platform. Through system development and user experience evaluation, this study seeks to provide a more efficient, integrated, and user-friendly solution for digital costume rental services. The research adopts a case study approach, focusing on system testing in a real-world environment. Data were collected through interviews with administrators and users, as well as system log analysis after implementation. The reduction in transaction processing time is based on a comparison of pre- and post- implementation data, where the average transaction time decreased from 10 minutes to 6 minutes. Additionally, a user satisfaction survey showed an increase in the average score from 3.8 to 4.5 (on a scale of 5) regarding ease of use and service speed. The conclusion of this study is that automation in a costume rental website not only enhances operational efficiency but also improves the quality of user interactions. Thus, implementing this technology has the potential to be a solution for similar industries to adapt to the demands of the digital market.